Strategi Luar Negeri Dubai Menjadi Sebuah Peradaban Modern (Melalui Kebijakan Luar Negerinya) - Nindyo Setiawan (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2017)
Located in the Middle East region, Dubai has to face the reality to compete with other countries in a business that only consists of the oil market. However, it was predicted that in the year of 2005, Dubai’s oil resources will be run out. After the establishment of United Arab Emirates (UAE), Dubai has slowly shown its progress significantly. Started as a desert civilization who didn’t have anything into a metropolitan country with all of the majesties which is considered as a world class level, often called as the Singapore of the Middle East. However, the success of Dubai can't be separated from the foreign policy created by its leader, Sheik Mohammed bin Rashid Al Maktoum who is often called as the CEO of Dubai. After pointed as the leader of Dubai Defense Force by his father, Sheikh Rashid, Sheikh Mohammed began to help his father. He finally took the position as Emir of Dubai in 2006 after his brother Maktoum bin Rashid Al Maktoum died. Through this paper, the writer is going explore the foreign policy created by Sheikh Mohammed bin Rashid al Maktoum. The analysis itself is going to use Idiosyncratic Theory created by Margareth Hermann as a theoretical framework.